Syntheses of Cyanophycin Segments for Investigations of Cell-Penetration - Grogg, Marcel; Hilvert, Donald; Beck, Albert K.; Seebach, Dieter (Synthesis, 2019)
Novel guanidinium-rich oligopeptide derivatives R-[Adp(X)]8-NH2 are described, which consist of an octa-aspartic acid backbone with argininylated side chains that are derived from the biopolymer cyanophycin [H-(Adp)n-OH]. The Fmoc-Adp(X,Pbf)-OH building blocks for solid-state peptide synthesis (SSPS) of Adp octamers were prepared from Fmoc-Arg(Pbf)-OH and Fmoc-Asp-OAll. Coupling on PAL resin provided four octamers with and without N-terminal fluorescent groups (FAM) and C-terminal amide groups. Milligram quantities of Adp-octamers were isolated after preparative HPLC purification. The structure of the novel guanidinium-rich oligomers is unique insofar as the side chains of the Asp8-backbone include both a guanidino and a carboxylic acid group, the influence of which will be tested with the corresponding ester and amide derivatives that were synthesized in parallel. Unusual cell-penetrating properties of the Adp-octamers are expected.
Keywords: guanidinium-rich oligopeptides; β3/α-Asp-Arg-dipeptide building block; biopolymer cyanophycin; solid-state peptide synthesis; cell-penetrating peptides